Genetic counselling: the psychological impact of meeting patients' expectations. Issue 3 (March 1997) - Michie, S; Marteau, T M; Bobrow, M
Abstract : We know little about patients' expectations of genetic counselling, the extent to which these are met, and whether meeting expectations is associated with improved patient outcome. This study describes 131 consultations of patients referred to a regional genetics centre, and documents their expectations, the extent to which these are met, and the predictors and consequences of expectations being met. The outcomes assessed were state anxiety, concern about the problem for which the patient was referred, and satisfaction with information given. Patients came to genetic counselling expecting information (79%), explanation (63%), reassurance (50%), advice (50%), and help in making decisions (30%). The majority got what they were expecting: 74% had their expectation for information met, 56% had their expectation for explanation met, 60% had their expectation for reassurance met, 61% had their expectation for advice met, and 73% had their expectation for help with making decisions met. Patient expectations, and whether or not these were met, were not predicted by any of the patient or counsellor variables measured. When patients' expectations for reassurance and advice were met, patients were less concerned and their anxiety level was more reduced than when such expectations were not met. Meeting patients' expectations for information, explanation, or help with decision making were not associated with better outcomes. Explanations for these results and implications for the practice of genetic counselling are discussed.